The Problem of Hidden Public Debt in Poland - Kasperowicz-Stępień, Alicja (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The largest problem facing Polish public finance today is the rapid growth in public debt and the attendant costs of servicing it. According to government calculations, in 2010 public debt reached 54.9% of GDP. Yet to the government calculations must be added hidden public debt, which actually measures 180% of GDP. This paper analyses the level of evident and hidden public debt in Poland.